Complete and early response to cemiplimab associated to severe immune toxicity in advanced cervical cancer: a case report - Passarelli, Anna; Pisano, Carmela; Coppola, Elisabetta; Ventriglia, Jole; Cecere, Sabrina Chiara; Di Napoli, Marilena; Carideo, Luciano; Lastoria, Secondo; Pignata, Sandro (Frontiers in Immunology, 2023)
Cervical cancer (CC) is the second most commonly diagnosed cancer and the third leading cause of cancer death among females. The options of treatment for recurrent/advanced CC are limited and patients experiencing recurrence after first line platinum-based chemotherapy have a poor prognosis. In this context, immune checkpoint inhibitors (ICI)s antagonizing PD-1 and programmed death-ligand 1 (PD-L1) have profoundly changed the treatment scenario and outcomes in CC in the first or subsequent lines both as monotherapies or in combination with chemotherapy or other ICIs. Herein, we report the clinical case of a 74-year-old woman with metastatic CC with negative tumor PD-L1 expression who having disease progression after first-line of systemic treatment with platinum, thus undergoing to anti-PD-1 namely cemiplimab. The patient achieved a surprising, fast and complete metabolic response to cemiplimab immediately discontinued after only two cycles due to the onset of rare and severe immune-related adverse events (irAE)s such cardiovascular toxicity and hypertransaminasemia. Despite this, thirteen months later, the patient remains disease-free despite cemiplimab was withdrawn.